Pengaruh Gratis Ongkir Dan Sistem Pembayaran Cash On Delivery-Cek Dulu (COD-Cek Dulu) Terhadap Minat Beli Pada E-Commerce Shopee - Wilda Julianti; Andang Fazri; Husni Hasbullah (Pusat Riset dan Inovasi Nasional, 2024)
This research is the result of quantitative research which aims to answer questions about the influence of free shipping and the COD-Cek Dulu payment system on buying interest in Shopee e-commerce. The population in this study are Shopee e-commerce users. The research methodology used is quantitative research and the sampling technique uses the snowball sampling method with a sample size of 96 respondents. The data collection technique uses a questionnaire with the help of a Google form which is processed using SPSS version 26 and the data analysis technique uses multiple linear regression.